Back‐Arc Extension of the Central Bransfield Basin Induced by Ridge–Trench Collision: Implications From Ambient Noise Tomography and Stress Field Inversion. Issue 21 (28th October 2021) - Li, Wei; Yuan, Xiaohui; Heit, Benjamin; Schmidt‐Aursch, Mechita C.; Almendros, Javier; Geissler, Wolfram H.; Chen, Yun
Abstract: The Bransfield Basin is a young (∼4 Ma) back‐arc basin related to the remnant subduction of the Phoenix Plate that once existed along the entire Pacific margin of the Antarctic Peninsula. Based on a recently deployed amphibious seismic network, we use ambient noise tomography to obtain the S ‐wave velocity structure in the Central Bransfield Basin (CBB). Combining with the stress field inverted from focal mechanisms, our images reveal that the CBB suffers a significant extension in the northwest‐southeast direction. The extension is strongest in the northeastern CBB with associated mantle exhumation and weakens to the southwest with decoupled deformations between the upper crust and lithospheric mantle. Such an along‐strike variation of extension can be explained by slab window formation and forearc rotation, which are associated with the Phoenix Plate detachment during the ridge–trench collisions at the southwest of the Hero Fracture Zone. Plain Language Summary: Crustal extensions behind volcanic arcs are commonly attributed to subduction processes, however, subduction alone is not sufficient to trigger the back‐arc extension as the latter is missing in some ongoing subduction zones. An effective way to assess the sufficient condition is to learn how the back‐arc extension initiates. Here, we examine the recently formed Central Bransfield Basin (CBB), located off the Antarctic Peninsula in the back‐arc setting of the Phoenix subduction zone. The stress field inverted from focal mechanisms indicates a northwest‐southeast extension in the CBB. S ‐wave velocity structures imaged by ambient noise tomography show that the extension has distinctly different degrees along the axis of the CBB, which is strongest with associated mantle exhumation in the northeast and gradually weakens toward the southwest. Our observations suggest that the back‐arc extension of the CBB, which started at ∼4 Ma, was initiated by the ridge–trench collision at the southwest of the Hero Fracture Zone. With the subduction zone progressively eliminated during the ridge–trench collisions, the subducted Phoenix Plate has detached along the segmental Phoenix‐Antarctic Ridge to form the slab window and trigger the forearc rotation, that initiated the back‐arc extension of the CBB. Key Points: S ‐wave velocity structures beneath the Central Bransfield Basin (CBB) and adjacent areas are obtained by ambient noise tomography The back‐arc extension is strongest in the northeastern CBB with associated mantle exhumation and gradually weakens toward the southwest The ridge–trench collision and subsequent detachment of the subducted Phoenix Plate initiated the back‐arc extension of the CBB